Analisis Strategi Penyusunan Prioritas Anggaran Kegiatan di Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Ogan Komering Ilir - Antoni, Antoni; Hestirinaih, Deby Chintia; Saswita, Saswita (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2026)
The purpose of this study was to analyze the Strategy for Prioritizing Activity Budgets at the Office of Public Works and Spatial Planning in Ogan Komering Ilir Regency. This research is a descriptive research with a qualitative approach. Data collection tools are observation, interviews and documentation. Informants in this study. Data analysis is a qualitative analysis with an interactive model. Based on the results of the study, it is known that the Prioritization of Activity Budgets at the Office of Public Works and Spatial Planning (PUPR) of Ogan Komering Ilir (OKI) Regency has been carried out in accordance with applicable procedures and regulations, although not yet optimal. Arrangement of Activity Budget Priorities at the Office of Public Works and Spatial Planning (PUPR) of Ogan Komering Ilir (OKI) Regency, including planning, implementation, financial administration, reporting, accountability and supervision activities. In this regard, there are several obstacles encountered in implementing the budget, namely the problem of time, human resources, and coordination between related parties.